Graph transformations in architectural design - Szuba, Janusz; Borkowski, Adam (Computer Assisted Methods in Engineering and Science, 2003)
This paper deals with computer-aided design of layouts of buildings. The methodology based upon graph grammars and graph transformations allows the designer to distract itself from details and to consider the functionality of the designed object, the constraints and the requirements to be met and the possible ways of selecting optimum alternatives. The specification of building is made in the UML with the aid of the FUJABA system. After this has been accomplished, a proper graph grammar is generated automatically. Such a grammar defines a class of objects that fulfill prescribed requirements and deliver required functionality. The user of the proposed system can browse members of that class, i.e. compare alternative plausible designs, using any commercially available visualization tool.